Segmentasi Kecamatan di Kota Bandung Berdasarkan Statistik Penyandang Disabilitas Menggunakan Algoritma K-Means Clustering - Rosni Rosni; Erinna Fredella; Muklas Rivai (FKIP Universitas Mataram, 2026)
People with disabilities continue to experience discrimination, stigmatization, and unfulfilled rights. The number of people with disabilities in Bandung City is the second highest in West Java Province. Various factors, including a disability-unfriendly environment, lack of accessibility to public infrastructure, and insufficient social support. This study aims to analyze and segment subdistricts in Bandung City based on disability statistics using the K-Means clustering algorithm. The types of disabilities analyzed include mental disabilities, physical disabilities, physical and mental disabilities, visual impairments, hearing impairments, and other types of disabilities. The results of the study showed that the optimal number of clusters, as determined by the Elbow method, is 2 clusters. A total of 18 subdistricts are classified into Cluster 1, characterized by a relatively lower number of persons with disabilities, while the remaining 12 subdistricts are classified into Cluster 2, which has a relatively higher number of persons with disabilities. The results of this segmentation are expected to support the realization of Bandung City as an inclusive city and to assist the government in developing more targeted policies and programs.